2023
DOI: 10.1177/09603271231160477
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Postconditioning Attenuates Cerebral Ischemia-Reperfusion Injury by Inhibiting SP1/ACSL4-Mediated Ferroptosis

Abstract: Sevoflurane is the most commonly used anesthetic in clinical practice and exerts a protective effect on cerebral ischemia-reperfusion (I/R) injury. This study aims to elucidate the molecular mechanism by which sevoflurane postconditioning protects against cerebral I/R injury. Oxygen-glucose deprivation/reperfusion (OGD/R) model in vitro and the middle cerebral artery occlusion (MCAO) model in vivo were established to simulate cerebral I/R injury. Sevoflurane postconditioning reduced neurological deficits, cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…ACSL4 has been reported could act as an essential component for ferroptosis execution and dictate ferroptosis sensitivity by shaping cellular lipid composition [ 11 ]. In vitro models, researchers found that transcription factor SP1 could bind directly to the ACSL4 promoter region to increase its expression [ 47 ]. Remarkably, SP1 was also a downstream protein of EGFR/p38-MAPK signaling, whose phosphorylation and activation were closely correlated to EGFR [ 48 , 49 ], implying that EGFR mutant could regulate ACSL4 expression by modulating SP1 phosphorylation and activation.…”
Section: Discussionmentioning
confidence: 99%
“…ACSL4 has been reported could act as an essential component for ferroptosis execution and dictate ferroptosis sensitivity by shaping cellular lipid composition [ 11 ]. In vitro models, researchers found that transcription factor SP1 could bind directly to the ACSL4 promoter region to increase its expression [ 47 ]. Remarkably, SP1 was also a downstream protein of EGFR/p38-MAPK signaling, whose phosphorylation and activation were closely correlated to EGFR [ 48 , 49 ], implying that EGFR mutant could regulate ACSL4 expression by modulating SP1 phosphorylation and activation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that SP1 is connected to oxidative stress and ferroptosis (Lyu and Li, 2023;Ma et al, 2022). Acsl4 have been identi ed as a target gene of SP1 (Deniaud et al, 2009).…”
Section: Sp1 Regulates Acsl4 Mrna and Protein Levels In Kgn Cellsmentioning
confidence: 99%
“…Ferroptosis has recently been increasingly recognized as an important mechanism of pathological cell death during stroke. Ferrostatin-1 [64] and its analog, Srs11-92 [65], can improve oxidative stress and neuroinflammation following cerebral I/R injury, potentially serving as novel targets for neuroprotection.…”
Section: Ferrostatin-1mentioning
confidence: 99%